Questionable Insiders: Changing Positionalities of Interviewers throughout Stages of Migration Research. Issue 3 (August 2019) - Pustulka, Paula; Bell, Justyna; Trąbka, Agnieszka
This article addresses methodological issues related to the consequences of researchers' range of insider identities that emerge over the course of completing subsequent stages of qualitative migration research projects. Taking on a temporal approach to the insider status evolving over the course of field entry, data collection, data analysis, and dissemination, this article engages with nuanced insider positionalities. These range from apparent, to trespassing, to distanced, and to ambassadorial insiderness. Exploring a specific case of Polish mobility, this article assumes a methodological focus and argues that being "on the inside" of the migration research field may go beyond gender, ethnicity, and social status when it is linked to a project's life cycle.